Сельские усадьбы Херсонеса Таврического в римское время. Итоги исследований украинско-польской экспедиции - Ковалевская, Л.А.; Сарновски, Т. (Боспорские исследования, 2010)
Целью данной статьи является представление предварительных результатов исследований сельской территории Херсонеса Таврического совместной украинско-польской экспедиции (Институт археологии Крымского филиала НАНУ и Институт археологии Варшавского университета). Проект охватывает памятники археологии Верхне-Юхариной балки на Гераклейском полуострове, где в настоящее время ведётся активное строительство, что нарушает сохранность древних сооружений. Статья представляет итоги исследований в 2005-2007 гг. пяти сельских усадеб (340,341,343,344,363). В работе представлены геодезические обмеры, пространственная модель рельефа местности, фотографии с небольшой высоты, геофизическая и археологическая проспекции, анализы костного материала и палеоботаники. Метою цієї статті є подання попередніх результатів досліджень сільської території Херсонесу Таврійського сумісною українсько-польською експедицією ( Інститут археології Кримської філії НАНУ та Інститут археології Варшавського університету). Проект охоплює пам’ятки археології Верхнє-Юхариної балки на Гераклейському півострові, де в даний час ведеться активне будівництво, що порушує збереження давніх споруд. Стаття подає підсумки досліджень у 2005-2007 рр. п’яти сільських садиб (340, 341, 343, 344, 363). В роботі подані геодезичні обміри, просторова модель рельєфу місцевості, фотографії з невеликої висоти, геофізична та археологічна проспекті, аналізи кісткового матеріалу та палеоботаніки. The aim of this paper is to present initial results of an ongoing interdisciplinary study by the Crimean Branch of the the Institute of Archaeology, the Ukrainian Academy of Sciences, and the Institute of Archaeology, the University of Warsaw, of the border zone of the rural territory of Tauric Chersonesos. The joint project is concentrated on archaeological features in the upper part of the Yukharin Ravine on the Heraklean Peninsula, where in recent years rapid suburban expansion and activity of local treasure hunters have seriously endangered still visible traces of ancient rural landscape. The paper gives a review of research carried out in 2005-2007 within five agricultural land plots (Farmhouses 340,341,343,344,363). The research includes geodetic mapping, remote sensing, geophysical prospection, archaeological survey and excavation, palaeobotanical and palaeozoological analyses.